Corredores y "gremios" (huiguan 會館) en el comercio marítimo de China con sus vecinos del este durante las dinastías Ming y Qing - Schottenhammer, Angela (El Colegio de México, 2010)
What were the organizational structures of China’s maritime trade with its eastern neighbours; and what was the relationship between governmental trade control mechanisms and private business that engaged in this sector of the market economy? How important were particular organizations such as the huiguan 會館 and yahang 牙行? This article addresses these issues by documenting in detail the cases of China’s Ming and Qing period trade relations with the Ryūkyūs as well as the Sino-Japanese copper trade during the high Qing. The article analyzes the complex relations and competition between government-controlled organizations like the broker houses that were supported by human resources outside the bureaucracy, private enterprises of business firms as well as native-place guilds. The public policy of control over maritime trade on the China coast was implemented not in a context of a zero-sum game between the interest of the state and that of the private sector. Rather, the policy ended up creating a structure where interests of both sides were compromised but served. The result was a favorable business environment for both the Fujian and the Jiangnan market economy, witnessed even in the more restricted sector of maritime trade under Qing rule.